The climate variability in northern Levant over the past 20, 000 years. Issue 20 (29th October 2015) - Cheng, H.; Sinha, A.; Verheyden, S.; Nader, F. H.; Li, X. L.; Zhang, P. Z.; Yin, J. J.; Yi, L.; Peng, Y. B.; Rao, Z. G.; Ning, Y. F.; Edwards, R. L.
Abstract: The Levant constitutes an important region for assessing linkages between climate and societal changes throughout the course of human history. However, large uncertainties remain in our understanding of the region's hydroclimate variability under varying boundary conditions. Here we present a new high‐resolution, precisely dated speleothem oxygen‐carbon isotope and Sr/Ca records, spanning the last 20 ka from Jeita Cave, northern Levant. Our record reveals a higher (lower) precipitation‐evaporation (P‐E) balance during the Last Glacial Maximum and Bølling interstadial (Heinrich stadial 1). The early‐middle Holocene is characterized by a trend toward higher P‐E state, culminating between ~7 and 6 ka. The middle‐late Holocene is characterized by two millennial‐length drier periods during 5.3–4.2 and 2.8–1.4 ka. On submillennial time scale, the northern Levant climate variability is dominated by 500 year periodicity. Comparisons with the regional proxy records suggest persistent out‐of‐phase climate variability between the northern and southern Levant on a wide range of timescales. Key Points: High‐resolution speleothem record is established in northern Levant in the last 20 ka The Climate variability on various timescales in northern Levant is characterized Climate variations are out of phase between northern and southern Levant